Towards a Sustainable Algiers: Analyzing Urban Typologies for Sustainable Cities (International Journal of Built Environment and Sustainability, 2025)
The rapid urbanization in Algeria has led to a focus on the forms and specifications of urban areas, particularly in Algiers, which necessitates innovative approaches for sustainable development. This study concentrates on Algiers, a city with a unique combination of architectural styles, encompassing various urban layouts, such as traditional Casbah, 19th-century colonial architecture, and modern structures. This study examines the sustainability and livability of each architectural typology through the application of a mixed-method approach that merges qualitative field observations with quantitative data sourced from academic publications. The findings revealed that each typology offers distinct sustainability advantages. These results emphasize the necessity of implementing a balanced urban development strategy that acknowledges historical contexts, while incorporating modern advancements to promote a sustainable future. This study provides essential insights into the relationship between urban typologies and sustainability in Algiers as well as the social impacts of each typology on citizen well-being and social cohesion.
Keywords: Algiers, Sustainability, Urban forms, Urban sustainability, Urban typologies